Disentangling ESG: Environmental, social and governance ratings and financial performance of Polish listed companies - Buła, Rafał; Foltyn-Zarychta, Monika; Krawczyńska, Dominika (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2024)
Socially responsible investments are a significant element of the global capital market and are becoming increasingly important also in the eyes of Polish investors. ESG ratings are a crucial decisive criterion, as they provide information on the corporate governance (G), and social (S) and environmental (E) activities, of companies. Even though the abovementioned areas differ significantly, the use of ESG ratings by investors is often narrowed down to the total ESG score. Additionally, the literature does not provide unambiguous results on whether the impact of total score as well as the individual pillars of E, S and G on the accounting-based financial performance of companies is statistically significant, and positive or negative. Sparse academic studies concentrate mainly on highly developed markets and accounting-based measures of profitability, leaving aside emerging markets, like Poland, and the other main characteristics of financial performance, like liquidity, efficiency, or leverage. The aim of this paper is therefore to fill the above gap by identifying the dependence of ratings in E, S and G areas and the accounting-based financial performance of companies listed on the Warsaw Stock Exchange. Selected financial parameters and company quotations were taken from the Notoria Serwis SA database, while data on ESG ratings from Refinitiv Eikon were used to perform correlation analysis. The analysis covers the years 2013–2022. The findings indicate a significant positive bi-directional impact of corporate governance (G) and efficiency, as well as of controversies score and efficiency. A linkage has also been revealed between controversies score and profitability. However, the hypothesis of an unequivocally positive impact of ESG factors on financial results, or conversely of financial results on ESG aspects, should be rejected.